Dyslipidemia Prevalence among Tinnitus Patients of a Referral ENT Clinic in Tehran, Iran, 2018 - Etemadi, Kourosh; Goljanian Tabrizi, Ali; Fahimi, Mahdieh (International Clinical Neuroscience Journal, 2019)
Background: Tinnitus is a common neurosensory disorder that can bring many problems such as stress and sleep disorders to the patients and affect their quality of life. Unfortunately, its pathophysiology has not been exactly discovered yet, but there have been some studies executed about the possibility of dyslipidemia causing tinnitus. Studying more on this subject and especially on the Iranian population in order to provide us with evidence-based information, can help us find the optimal method to control and treat this disorder. Methods: In this study, 76 patients that have had complaints of tinnitus in the ENT (ears, nose, and throat) clinic of Taleghani hospital, Shahid Beheshti University of Medical Sciences, in the year 2018, were selected. Also, after taking a history about the severity and the onset of their problem, they were examined and also blood samples were taken to check their lipid profiles. Finally, the results of the lab tests, the severity and the onset of their disorder and also their age and sex were statistically analyzed. Results: The study showed that the prevalence of dyslipidemia in patients with tinnitus is not significantly greater than its prevalence in the general population. Furthermore despite the relationship between dyslipidemia and the onset and severity of the tinnitus is not significant, the effect of dyslipidemia on tinnitus shows itself after about one year and a half (P=0.000), it means dyslipidemia does not cause the tinnitus but affects in its duration. It also indicated the most common type of dyslipidemia among the patients that we studied, was Hypercholesterolemia with the prevalence of 23.68%. Conclusion: The Study suggests that despite the Hypercholesterolemia prevalence of 23.68% among these patients, dyslipidemia does not have a significant relationship with the severity of the neuro-sensory disorder “tinnitus’ overall, but dyslipidemia affects tinnitus after suffering for about one year and a half. Therefore there will not be a need to use blood tests in order to measure the lipid profile factors at the beginning and the first months of the patients’ tinnitus.